A comparative study of viral infectivity, accumulation and symptoms induced by broad bean wilt virus 1 isolate - Carpino, Caterina; Elvira-González, Laura; Rubio, Luis; Peri, Ezio; Davino, Salvatore; Galipienso, Luis (Springer, 2020)
Broad bean wilt virus 1 (BBWV-1, genus Fabavirus, family Secoviridae) is a bipartite positive-sense single-stranded RNA virus distributed worldwide infecting many herbaceous species. Until now, scarce information regarding biological properties of BBWV-1 isolates is available. This work shows a comparative study on virus infectivity (proportion of infected plants over inoculated plants), virus accumulation and symptoms induced by four genetically different BBWV-1 isolates (Ben, B41/99, NSRV and PV0548) which were mechanically inoculated on several herbaceous hosts. The four BBWV-1 isolates infected broad bean, tomato, pepper and Nicotiana benthamiana plants, whereas none of them infected cucumber, common bean and melon. Infectivity ranged from 40 to 60% in tomato and from 75% to 95% in pepper, whereas it was 100% in broad bean and N. benthamiana for the four BBWV-1 isolates. Symptoms showed differences depending on the host plant, the viral isolate and the infection time. Virus accumulation was determined in broad bean and pepper plants and showed differences among host species and BBWV-1 isolates. No association between plant symptom manifestation and viral titre was observed.